Experimental approach to extend the range for counting fluorescent molecules based on photon-antibunching - Ta, Haisen; Kiel, Alexander; Wahl, Michael; Herten, Dirk-Peter (Physical chemistry, chemical physics, 2010)
In single-molecule fluorescence spectroscopy photon-antibunching is frequently used to prove the occurrence of single fluorophores. Furthermore, the relative frequency of coincident photon pairs was also used to determine the number of fluorophores in the diffraction limited observation volume of a confocal microscope. However, the ability to count fluorophores is so far limited to ∼3 molecules due to saturation of the calibration curve with increasing number of fluorophores. Recently, we introduced a novel theoretical framework for counting the number of emitting molecules by analyzing photon-distributions acquired with a confocal microscope using four single-photon detectors. Here, we present the experimental realization of the proposed scheme in a confocal setup using novel multi-channel photon-counting electronics and DNA constructs that were labelled with five fluorophores. Our experimental results give a clear correlation between the number of estimated fluorophores and the number of bleaching steps for DNA probes conjugated with five ATTO647N labels with an error of ∼20%. Moreover, we could acquire experimental data for up to 15 fluorophores indicating the simultaneous occurrence of three DNA probes. Our experiments put into perspective that the analysis of photon-distributions acquired with four detection channels is suited to count the number of fluorescently labelled molecules in larger aggregates or clusters with potential for applications in molecular and cell biology and for time-resolved analysis of multi-chromophoric compounds in material sciences.